Optimizing thermoplastic composites manufacturing process for homogeneity and continuity - Huang, Xuan Ai (Nanyang Technological University, 2024)
This research aims to optimize the manufacturing process of thermoplastic composites to achieve unparalleled levels of homogeneity and continuity, thereby enhancing the mechanical properties and overall quality of the final composite product. The current filament winding fabrication technique poses significant challenges marked by the presence of voids and porosity, which adversely impacts the structural integrity and strength of the material. The methodology focuses on optimizing key parameters within the ComposiCAD software. This process involves the refinement of variables such as adjustment to the width of the glass fibre- nylon6 (GF-PA6) and carbon fibre-nylon 6 (CF-PA6) commingled yarn, along with other configurations to minimize presence of voids and porosity. Moreover, this research systematically streamlines the manufacturing stages involved. Redundant stages are identified and eliminated for more efficient utilization of resources, thus, optimising the overall production process. The product is subjected to both porosity and compression tests which are done to evaluate the effectiveness of the optimized parameters. Preliminary findings have shown promising results, indicating a significant reduction in the percentage of voids by over 30% and a remarkable 3.5 times improvement on the compressive strength of the composite material. These positive results underscore the potential impact of the meticulous efforts made in optimizing every aspect of the manufacturing process. Further research focusing on the refinement and advancement in the manufacturing process of thermoplastic composites are fundamental in pushing the boundaries for even greater homogeneity and continuity of the materials.